Egypt’s Strategic Hedging in Economics with the United States and China from 2014-2024 - Flynn, Abigail (AUC Knowledge Fountain, 2026)
This research aims to explain how Egypt is able to engage economically with two internationally competitive powers, the United States and China, using the theoretical framework of strategic hedging in the period of 2014-2024. While existing literature on strategic hedging is primarily focused on Southeast Asia and broadly deals with political hedging, this study applies the framework specifically to Egypt and is limited to economic relations. This research is significant because it identifies how Egypt is able to increase its economic engagement with the U.S. and China despite their competitive status and offers a novel argument which can be tested with any small state courting two larger, competitive powers. This study is explanatory and takes a mixed-methods approach, using content analysis of Egypt’s government publications on the issue of economic relations with both countries in addition to quantitative analysis of its economic relations with both in regards to trade, investments, and loans. This study concludes that Egypt is able to court two competitive powers because they occupy separate areas of the Egyptian market; however, it notes that the Egyptian trend over the past two years toward de-dollarization may open a future point of competition that may disrupt this balance. Ultimately, this research contributes to the growing discourse on how small states can achieve their strategic goals in an increasingly multipolar world by providing a novel argument which can be applied in many settings.